Coke formation and utilization during coke oven gas reforming–CO2 splitting cycles over spherical SrFeO3 pellets for syngas and CO production - Sang-Hyeok Kim; Seolhwa Yun; Jung-Hyun Lee; Il-Hyun Baek; Sung-Chan Nam; Jong Tak Jang (Journal of CO2 Utilization)
Spherical SrFeO3 pellets are used for effective syngas and CO production during coke oven gas reforming (COGR) and CO2 splitting (CS), exhibiting a high CH4 oxidation activity and suppressing reduction by H2 and CO during methane reforming (MR). Above 850 °C, MR produces H2-rich syngas through simultaneous reduction and CH4 decomposition reactions. For sequential CS, CO production is amplified owing to the co-occurrence of CO2 splitting and reverse Boudouard reactions. The redox reaction time is optimized to realize MR–CS cycling with a high redox stability and coke utilization efficiency. From the third MR–CS cycle onward, the reoxidation percentage exceeds 96.4 %, consistent with crystal structure evolution. Amorphous carbon is deposited on SrFeO3−δ via the decomposition of CH4 during MR, and the content of this carbon remains constant after the 10th MR–CS cycle because of its high reactivity toward CO2. Over 10 COGR–CS cycles, superior coke utilization due to the occurrence of the reverse Boudouard reaction during COGR results in stable syngas and CO production from the second cycle onward.